ANALISIS PENALARAN SISWA DALAM MENYELESAIKAN MASALAH BANGUN DATAR DITINJAU GAYA BELAJAR DAN MOTIVASI BELAJAR SISWA SMP - Azizah, Putri Nur; Sa’dijah, Cholis; Sudirman, Sudirman (Universitas Bhinneka PGRI, 2026)
It is important for students to have reasoning skills in learning mathematics. This is due to the relationship between mathematics and reasoning. This research aims to determine students' reasoning abilities in solving flat shape problems in terms of learning styles and learning motivation of junior high school students. This type of research is descriptive qualitative. The subjects in this research consisted of six class VIII students selected from a junior high school in Malang City, namely one student with a visual learning style and high learning motivation; one student from a visual learning style and low learning motivation; one student from an auditory learning style and high learning motivation; one student from an auditory learning style and low learning motivation; one student from the kinesthetic learning style and high learning motivation and one student from the kinesthetic learning style and low learning motivation. Research data was taken from learning style questionnaires, learning motivation questionnaires, written tests and interviews. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The research results showed that students who had visual, auditory and kinesthetic learning styles with high learning motivation met all the reasoning indicators, while students who had visual, auditory and kinesthetic learning styles with low learning motivation did not meet all the reasoning indicators.